2020
DOI: 10.1080/21645515.2020.1717184
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese nationwide survey of 23-valent pneumococcal capsular polysaccharide vaccine (PPSV23) revaccination coverage rate among elderly adults aged 65 and older and physician’s attitude

Abstract: In July 2017, the Japanese Association for Infectious Diseases issued guidance for the administration of the PPSV23 revaccination. Despite increasing recognition of its protective benefits, levels of PPSV23 revaccination coverage rate in Japanese elderly population are unclear at present. Here, we report the results of a survey to know PPSV23 revaccination rates among elderly patients aged 65 and older. We asked an array of questions related to PPSV23 revaccination to Elderly adults and doctors across Japan vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“… 36 , 39 , 40 , 43-45 , 54 , 68 , 69 , 80 , 82 , 84 , 85 , 87 , 89-91 Eight of the studies found that recommendations from relatives had a positive influence on vaccination. 45 , 54 , 68 , 78 , 88 , 89 , 91 , 92 Conversely, five studies indicated lack of recommendation from HCPs 35 , 81 , 85 had a negative correlation with vaccination and two studies found discouragement from an HCP was the main reason for not vaccinating. 67 , 90 From the HCP perspective, three studies surveyed HCPs on providing recommendations for vaccinations; 54 , 82 , 91 among them it was found that doctors who regularly prescribed pneumococcal vaccination also encouraged revaccination 91 in Japan, where there are guidelines for HCPs to revaccinate adults aged 65 years and older.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“… 36 , 39 , 40 , 43-45 , 54 , 68 , 69 , 80 , 82 , 84 , 85 , 87 , 89-91 Eight of the studies found that recommendations from relatives had a positive influence on vaccination. 45 , 54 , 68 , 78 , 88 , 89 , 91 , 92 Conversely, five studies indicated lack of recommendation from HCPs 35 , 81 , 85 had a negative correlation with vaccination and two studies found discouragement from an HCP was the main reason for not vaccinating. 67 , 90 From the HCP perspective, three studies surveyed HCPs on providing recommendations for vaccinations; 54 , 82 , 91 among them it was found that doctors who regularly prescribed pneumococcal vaccination also encouraged revaccination 91 in Japan, where there are guidelines for HCPs to revaccinate adults aged 65 years and older.…”
Section: Resultsmentioning
confidence: 97%
“… 45 , 54 , 68 , 78 , 88 , 89 , 91 , 92 Conversely, five studies indicated lack of recommendation from HCPs 35 , 81 , 85 had a negative correlation with vaccination and two studies found discouragement from an HCP was the main reason for not vaccinating. 67 , 90 From the HCP perspective, three studies surveyed HCPs on providing recommendations for vaccinations; 54 , 82 , 91 among them it was found that doctors who regularly prescribed pneumococcal vaccination also encouraged revaccination 91 in Japan, where there are guidelines for HCPs to revaccinate adults aged 65 years and older. 93 Additionally, non-vaccination of patients was associated with providers not regularly advising vaccination (i.e., at the first visit within an accounting period) or when the provider reported neutral (as opposed to positive or negative) feelings about vaccination counseling.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Under the National Immunization Program, the coverage rates of PPV23 vaccine for the elderly were reported as 32–38% after 2014 and PCV13 vaccine for children as 95–100% (after 2013) [ 66 ]. Another study reported the coverage of PPV23 and PCV13 vaccines for elderly in 2018 as 32% and 0.7%, respectively [ 67 ]. Also, of note, case definition of IPD has changed in November 2016 with the addition of the detection of bacteria from other sterile sites other than blood and spinal fluid to the notification criteria.…”
Section: Discussionmentioning
confidence: 99%